127k views
4 votes
What value of x makes the equation 3(x-6)-8x= -2+5(2x+1) true

User PureGero
by
5.9k points

1 Answer

5 votes

Answer:

x= −7/5

Explanation:

Step 1: Distribute and combine like terms

3(x−6)−8x=−2+5(2x+1)

(3)(x)+(3)(−6)+−8x=−2+(5)(2x)+(5)(1)(Distribute)

3x+−18+−8x=−2+10x+5

(3x+−8x)+(−18)=(10x)+(−2+5)(Combine Like Terms)

−5x+−18=10x+3

−5x−18=10x+3

Step 2: Subtract 10x from both sides.

−5x−18−10x=10x+3−10x

−15x−18=3

Step 3: Add 18 to both sides.

−15x−18+18=3+18

−15x=21

Step 4: Divide both sides by -15.

Hope this helps! :)

User Yauheni Sivukha
by
6.1k points